Efficacy of Add-on Pregabalin in the Treatment of Patients with Generalized Anxiety Disorder and Unipolar Major Depression With an Early Nonresponse to Escitalopram: A Double-Blind Placebo-Controlled Study - Fountoulakis, Konstantinos N.; Karavelas, Vangelis; Moysidou, Stefania; Mavridis, Dimitris; Pastiadis, Konstantinos; Petalidou, Nicole; Nimatoudis, Ioannis; Kasper, Siegfried (Pharmacopsychiatry, 2019)
Introduction This study tests the efficacy of pregabalin versus placebo as adjunctive treatment in patients with generalized anxiety disorder (GAD) comorbid with unipolar major depression (UMD) and with an early nonresponse to escitalopram.Methods This is a double-blind, placebo-controlled 8-week add-on study of pregabalin, 75–600 mg/day (n=31) versus placebo (n=29) on open-label escitalopram in outpatients meeting the DSM-IV-TR criteria for GAD and UMD. The main outcome measures were change from baseline to endpoint in total STAI-S, Trail-Making Test B (TMT-B) and the Center of Epidemiological Studies Depression Scale (CES-D). Also changes in the parameters of the pupil’s reaction to light stimuli.Results There was no significant difference in any of the primary or secondary outcomes or response and remission rates concerning any analysis (last observation carried-forward of at least visit 2 or completers) between the 2 treatment arms. One additional finding of the current study is that adding pregabalin does not have a significant effect on autonomic function.Discussion This study does not support the usefulness of adding pregabalin in patients with GAD and UMD and with an early nonresponse to escitalopram (EudraCT Number: 2012-004062-17, Sponsor’s Protocol Code Number: WS1702721).
Keywords: add-on; pregabalin; generalized anxiety; depression; escitalopram